Pocket park as an urban place-making - Mohd. Hussain, Mohd. Ramzi; Mohd Fazir, Nor Fatin Diana; Zainan, Nadia Aqma (International Journal of Multidisciplinary Sciences and Advanced Technology, 2020)
The paper presents the theoretical framework of what is the potential of a pocket park as an urban place-making. The paper is divided into three main sections which is section 1 discusses the introduction of the pocket park, which includes the definition, types and the elements that can be found at the pocket parks. In section 2, the pocket park is further elaborated as a space in an urban area, which explains the functions, characteristics and the importance of pocket park in the urban area. Section 3, will clarify what is the pocket park as an urban place-making, which explains the concept, roles and examples of activities and townscape in the pocket park for urban place-making. Based on the reviews, it is hoped that the paper will be a useful addition to the body of knowledge on the potential of a pocket park as a public realm to create an urban place-making.